The role of admission electrocardiogram in predicting outcome in patients hospitalized for COVID-19 - Zeijlon, Rickard; Hällgren, Peter; Le, Vina; Chamat, Jasmina; Wågerman, Johan; Enabtawi, Israa; Rawshani, Araz; Unenge, Sten; Jha, Sandeep; Omerovic, Elmir; Redfors, Björn (Journal of electrocardiology, 2022)
Abnormal electrocardiogram (ECG) has been associated with poor outcome in patients hospitalized for COVID-19. However, the independent association between admission ECG and the risk of a poor outcome remains to be established. Our aim was to determine if abnormal admission ECG predicts treatment at intensive care unit or in-hospital death within 30 days in patients hospitalized for COVID-19. We analyzed the propensity weighted association between abnormal admission ECG and outcome in patients hospitalized for COVID-19 (March to May 2020). All adult patients hospitalized for COVID-19 at the three centers of Sahlgrenska University Hospital (Gothenburg, Sweden) were eligible for inclusion (N = 439). Patients with available admission ECG within six hours from admission were included. 238 patients (age 62 ± 16 years, 74% male) were included. 103 patients had normal ECG and 135 patients had abnormal ECG. 99 patients were admitted to intensive care unit or died in-hospital within 30 days. Abnormal ECG was associated with increased risk of the outcome (odds ratio 2.11 [95% confidence interval 1.21–3.66]). Abnormal admission ECG was associated with increased risk of treatment at intensive care unit or in-hospital death within 30 days; and could be considered a high-risk criterion in patients hospitalized for COVID-19.